Leveraging Immunotherapy with Nanomedicine. Issue 12 (30th September 2020) - Mittelheisser, Vincent; Banerjee, Mainak; Pivot, Xavier; Charbonnière, Loïc J.; Goetz, Jacky; Detappe, Alexandre
Abstract: Considerable progress has been made in the development and understanding of immunotherapy, notably with the emergence of novel chimeric antigen receptor T cells (CAR‐T) which changed the perception of personalized therapy. However, cell‐based immunotherapy not only lacks therapeutic efficiency in various solid cancers but also raises concerns related to important side effects. The convergence of immunotherapy and nanomedicine is timely as nanoparticles can now be easily conjugated to various antibodies and peptides enabling outstanding abilities to target specific cell populations in vivo. Here, the state of the art of immunonanotherapy that activates the immune system in vivo, by acting either as vaccines or as tumor microenvironment (TME) activators is described. Then, the development of ex vivo immune‐cell surface labeling strategies is discussed to exploit immune cells as trojan horses and thereby improving the delivery of the therapeutics in the TME. Such a strategy is likely to considerably amplify the efficacy of immunotherapy. Abstract : Nanoparticles have been widely employed to improve immunotherapy therapeutic efficiency. This review article describes how the new concept of immunonanotherapy can foster improved immune cell‐based therapy and overcome its usual therapeutic‐limiting secondary effects. The remaining challenges of these novel approaches such as their scalability and the feasibility of their clinical translation are also discussed.